2020
DOI: 10.1111/scs.12834
|View full text |Cite
|
Sign up to set email alerts
|

Humanistic caring, a nursing competency: modelling a metamorphosis from students to accomplished nurses

Abstract: Humanistic caring, a nursing competency: modelling a metamorphosis from students to accomplished nurses Background: Most nursing regulatory bodies expect nurses to learn to be humanistic and caring. However, the learning process and the developmental stages of this competency remain poorly documented in the nursing literature. Methods: The study used interpretive phenomenology, and 26 participants (students and nurses) were individually interviewed. Benner's (1994) method was adapted and concretised into a fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 25 publications
3
31
0
1
Order By: Relevance
“…However, two studies (Massé, 2016;Oja, 2013) reported a development of communication skills in externs who completed their program. Although humanistic caring cannot be solely reduced to communication skills (Létourneau et al, 2021a), the findings of the present study corroborate the perception that externships may support this development. As mentioned by the participants, a humanistic and caring approach in educators was recommended and this holds true to externship experiences as well.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, two studies (Massé, 2016;Oja, 2013) reported a development of communication skills in externs who completed their program. Although humanistic caring cannot be solely reduced to communication skills (Létourneau et al, 2021a), the findings of the present study corroborate the perception that externships may support this development. As mentioned by the participants, a humanistic and caring approach in educators was recommended and this holds true to externship experiences as well.…”
Section: Discussionsupporting
confidence: 87%
“…Even though the interviewees were invited to share their inputs for both educational and clinical settings, they significantly had more recommendations for the education program. This finding was unexpected because other results from the same study underscored that the development of humanistic caring was considerably circumscribed by experiences lived through their internships or clinical practice Létourneau et al, 2021a). To explain this difference, it is possible that students and nurses felt it was more "realistic" to change aspects of the undergraduate program rather than suggesting adjustments for diverse clinical environments.…”
Section: Discussionmentioning
confidence: 87%
“…Although medical education and clinical practice pay more and more attention to integrate the concept of humanistic care into personal ability development and clinical work practices (such as the establishment of patient-doctor relationship, patient treatment and rehabilitation, and colleague relations, etc. ), and some progress has been made, but it is undeniable that drug therapy is still the subject of mental health [2,27,28]. In addition, Létourneau et al [27] also pointed out that the doctors or nurses who have just entered the clinic may voice their desire to provide humane care and maintain the ideal of humanistic practice, but perhaps because of work overload or fear of crossing the 'professional boundaries' due to "too close" to their patient.…”
Section: Discussionmentioning
confidence: 99%
“…), and some progress has been made, but it is undeniable that drug therapy is still the subject of mental health [2,27,28]. In addition, Létourneau et al [27] also pointed out that the doctors or nurses who have just entered the clinic may voice their desire to provide humane care and maintain the ideal of humanistic practice, but perhaps because of work overload or fear of crossing the 'professional boundaries' due to "too close" to their patient. There is a distance between their desire and practice, which hinders the further development of humanistic care ability.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this paper is to report on nursing students' and nurses' lived experiences that facilitate and hinder the development of humanistic caring. These phenomenological results are part of a larger study whose purpose was to develop a cognitive learning model (Goudreau, Boyer, & Létourneau, 2014;Tardif, 2006) of the humanistic caring competency, which is reported in another publication (Létourneau, Goudreau, & Cara, 2020).…”
mentioning
confidence: 97%